GE_GERICHTE C/2807/2017 vom 15. September 2017 - GE Cour de justice (2017)
MAINLEVÉE PROVISOIRE ; TITRE DE MAINLEVÉE ; CONTRAT D'ENTREPRISE ; DÉFAUT DE LA CHOSE ; INTERPRÉTATION(SENS GÉNÉRAL) | LP.82.1; LP.82.2;